2012
DOI: 10.26719/2012.18.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the spread of dengue fever in Jeddah Governorate, Saudi Arabia

Abstract: Dengue fever resurged sharply in Jeddah in 2004 and rose to 1308 cases in 2006. This case-control study determined factors potentiating the spread of the disease to provide an epidemiological baseline to help dengue control. All (650) suspected cases of dengue in Jeddah in 2007 were eligible for inclusion. Cases were those confirmed with dengue by laboratory investigations (n = 244) and controls those confirmed negative (n = 406). Of these, 129 cases and 240 controls could be contacted and were included in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 15 publications
4
23
0
Order By: Relevance
“…This study describes the clinical features and outcome of 567 patients admitted with proven dengue infection to a specialty hospital in Jeddah, Saudi Arabia from 2010 to 2014. In keeping with most previous studies, 24 - 26 85% of patients in this study were adults with a mean age of 34 years, while only 15% were children with a mean age of 7 years. Again in agreement with these previous reports, more male than female patients presented.…”
Section: Discussionsupporting
confidence: 91%
“…This study describes the clinical features and outcome of 567 patients admitted with proven dengue infection to a specialty hospital in Jeddah, Saudi Arabia from 2010 to 2014. In keeping with most previous studies, 24 - 26 85% of patients in this study were adults with a mean age of 34 years, while only 15% were children with a mean age of 7 years. Again in agreement with these previous reports, more male than female patients presented.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, male patients were more infected (74%); this is also noticed in other studies from Makkah and Jeddah (males were 51%-67%) [9,10,11,12]. Contrary to that, females were more often infected than males in a study from Brazil (females 59.3%) [13].…”
Section: Discussionsupporting
confidence: 84%
“…Two clinical studies found that fever, nausea, vomiting, headache, musculo-skeletal pain, and abdominal pain were common clinical symptoms [17,18]. A similar study in Pakistan found that abdominal pain, nausea, epistaxis and rash were the most frequent clinical symptoms (p < 0.05) [27].…”
Section: Discussionmentioning
confidence: 97%
“…A case-control study conducted in 2012 reported the following significant risk factors for DF: presence of stagnant water in indoor drainage holes, indoor larvae, nearby construction sites, and old age [18].…”
Section: Risk Factors From Studies Of Infectionsmentioning
confidence: 99%